Nocebo Effects and Negative Suggestions in Daily Clinical Practice – Forms, Impact and Approaches to Avoid Them - Hansen, Ernil; Zech, Nina (Frontiers in Pharmacology, 2019)
Medical situations are hot spots in the life of a patient with potentially long lasting effects arising from the use of either negative expressions or encouraging statements, or the lack of empathy or a positive physician-patient relationship. Health care personnel should be aware of and evaluate what patients are exposed to, hear and see. Knowing more about the effects of nocebos and negative suggestions, combined with increased attention to these matters, provides the basis for better recognition of detrimental influences in their own clinical environment and to be able to avoid, stop or neutralize them. After anamnesis patients should not be left with a focus on a negative past, but shifted to positive experiences prior to their illness, or to positive expectations in the future following surgery and rehabilitation. For example, after examining an injured leg the doctor should not turn to the computer for documentation unless he has shifted the patient’s focus on the other, unimpaired leg. “Is that painful too? No? Good! Can you feel that? Yes? Perfect! Can you bend that knee, move these toes? Great! That’s good.” This example draws attention to the fact that negative effects (discussed in the following) substantially are dependent on the focus of the patient and thus can be affected by focus shift and distraction. Patients, their symptoms and their healing are negatively affected by the omission of placebo effects, by nocebo effects and by negative suggestions.